Working from Within: Observations of Non-Governmental Efforts to Decrease Social Marginalization in Buenos Aires - Elisabeth Tilstra (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
This essay is a modification of an excerpt from the senior thesis written for the Chancellor’s Honors Program at The University of Tennessee. The complete project—titled “Bringing the Outside In: An Examination of Non-Governmental Aid Organizations in Buenos Aires”—first examines the political and economic history of Argentina as a context from which to understand the current stage of actors in the social sector. Then, drawing from my fieldwork in the slums surrounding urban Buenos Aires, it introduces the twelve organizations I studied that work with issues of poverty and development, exploring organizational elements that aid or limit a nonprofit’s efficacy. Finally, it concludes with my own project proposal; a submission of a way to incorporate the most effective elements into one organization. As this paper is just a piece of a larger work, I have chosen to highlight only the data from my time spent in Buenos Aires in 2011, leaving out the introductory sections that give political and economic context, as well as the project proposal. This paper assumes the economic context as briefly mentioned above, and focuses wholly on the characteristics of the studied organizations, and how they enhance – or hinder – organizational efficacy. It examines the structure and program implementation of these organizations, critically reviewing them as agents of change.
Keywords: Buenos Aires; Government; Poverty; Human Rights